Maximal metabolic responses of deep and shallow water running in trained runners - Town, G. P.; Bradley, S. S. (Medicine & Science in Sports & Exercise, 1991)
Maximal metabolic responses of competitive runners (N = 9) were compared for treadmill running, deep water running, and shallow water running. Results: Treadmill running elicited higher VO2max and HRmax than either water test. VO2max was higher for shallow water than deep water running. Respiratory exchange ratio and lactic acid measures did not differ between the conditions.